Effects of a mindfulness-based intervention on experienced job charachteristics : comparing the intervention group and the control group - Trifoglio, Valentina (2016)
The aim of this study was to investigate the effects of an 8-week mindfulness intervention on experienced job characteristics, which included job clarity, job satisfaction, workload and job control. Furthermore background factors, such as changes in private life, were examined as moderators of changes. This study included 155 participants (mindfulness group n=82, control group n=73) belonging to the group of most burnout workers in Finland. The 8-week intervention consisted of weekly group meetings and daily mindfulness and ACT based homework, whereas the control group received treatment usually offered for burnout. Assessment was based on personalized web questionnaires delivered at three time points (pre, post and follow-up). Results were analyzed with a test of repeated measures of ANOVA. Both groups experienced job characteristics in a more positive way during the intervention period; however positive changes in the intervention group were significantly greater compared to the control group. Regarding background factors group differences were found in a change in private life, changing the workplace and a change in work circumstances. Results suggest that mindfulness protects from difficult events in life and that a change of perspective is needed for a comprehensive change toward occupational well-being to occur. Mindfulness is effective in changing one’s perspective by increasing awareness in the present moment, by changing one’s attitude and by helping recognizing and disengaging from unhelpful thoughts and habits. Further investigation is needed to examine how long lasting the effects of mindfulness are during a longer period of time and to confirm the results implying that mindfulness protects from difficult events and changes in life.